Fractionation and identification of the nucleic acid-related substances secreted by Streptomyces aureofaciens - de Carvalho, Alírio; Malavolta, Cristina Marques; Quirino, Gustavo Hoff; Fernandes, José Atanasio dos Santos; Mengatti, Jair; Contiero, Jonas; Oppermann, Heloísa Ribi; Molinari, Rubens (Eclética Química, 1996)
.